Application of immunomagnetism for antigen preparation and cell selection in the creation of hybridomas - Qi, Chong Qing, 1954- (1993)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1993. Medicine Bibliography: leaves 101-109. Pagination error: page 1 is mislabeled xi. As part of a larger program to make monoclonal antibodies to HLA-DP polymorphisms, the possibility of using immunomagnetism to replace some cumbersome procedures in hybridoma creation was investigated. In the first part of this study, metallic beads were coated with anti-DP capture antibody and then were used for immune absorption of DP molecules from cell lysates. The absorbed molecules were identified with the help of a fluorescent anti-DP antibody and flow cytometry. Optimum conditions for absorption of DP molecules onto beads were worked out. In the second part, the immunogenic properties of the purified DP molecules were tested, in which metallic beads coupled with absorbed molecules were injected into mice to provoke an immune response. Serum antibody corresponding to three different antigen doses was determined and showed that the strong antibody response was correlated with the large dose of antigen. The influence of beryllium sulphate and complete Freund's adjuvant on these antibody responses was compared. In the final part of the study, immune spleen cells were sorted by using goat anti-mouse IgG coated metallic beads and/or antigen coupled beads. Following magnetic separation the selected spleen cells were fused with SP2/o myeloma cells without the detachment of the beads, using a centrifugal-electrofusion technique. Hybridomas which secreted antibodies were examined for their specificity to DP polymorphisms. The frequency of positive hybridomas, in fusions of pre-selected cells, was compared with that of the fusion of unsorted cells (prior to selection) and with that of the remainder of the cells left behind after a sort. Once a variety of tissue culture problems had been resolved, there was preliminary evidence suggesting that pre-fusion selection of antigen-specific cells can be a helpful and time-saving procedure.